Intraoperative Channeling in Arthroscopic Rotator Cuff Repair: A Multicenter Randomized Controlled Trial. Issue 2 (February 2023) - Lapner, Peter; Bouliane, Martin; Pollock, J W.; Coupal, Stephanie; Sabri, Elham; Hodgdon, Taryn; Old, Jason; Mcilquham, Katie; MacDonald, Peter; ,; Stranges, Greg; Berdusco, Randa; et al.
Background: Despite recent advances in arthroscopic rotator cuff repair, the retear rate remains high. New methods to optimize healing rates must be sought. Bone channeling may create a quicker and more vigorous healing response by attracting autologous mesenchymal stem cells, cytokines, and growth factors to the repair site. Hypothesis: Arthroscopic rotator cuff repair with bone channeling would result in a higher healing rate compared with arthroscopic rotator cuff repair without adjuvant channeling. Study Design: Randomized controlled trial; Level of evidence, 1. Methods: Our primary objective was to compare healing rates in patients undergoing arthroscopic rotator cuff repair for degenerative tears, with and without bone channeling. Secondary objectives included comparisons of the Western Ontario Rotator Cuff Index (WORC) score, American Shoulder and Elbow Surgeons (ASES) score, Constant score, Constant strength subscore, and visual analog scale (VAS) for pain score between groups. Patients undergoing arthroscopic rotator cuff repair were recruited at 3 sites and were randomized to receive either bone channeling augmentation or standard repair. Healing was determined via ultrasound at 24 months postoperatively. WORC, ASES, and Constant scores were compared between groups at baseline and at 3, 6, 12, and 24 months postoperatively. Results: A total of 168 patients were enrolled between 2013 and 2018. Intention-to-treat analysis revealed no statistical differences in healing rates between the 2 interventions at 24 months postoperatively. Statistically significant improvements occurred in both groups from preoperatively to all time points for the WORC, the ASES score, the Constant score or Constant strength subscore, and the VAS for pain ( P < .0001). No differences were observed between the bone channeling and control groups in WORC, ASES, Constant, and VAS pain scores at any time point. Conclusion: This trial did not demonstrate the superiority of intraoperative bone channeling in rotator cuff repair over standard rotator cuff repair at 24 months postoperatively. Healing rates, patient-reported function, and quality-of-life outcomes were similar between groups. Registration: NCT01877772 (ClinicalTrials.gov identifier).